2006
DOI: 10.1089/oli.2006.16.115
|View full text |Cite
|
Sign up to set email alerts
|

Conserved MicroRNA Characteristics in Mammals

Abstract: Short hairpin RNAs (shRNAs) and short interfering RNAs (siRNAs) probably enter different stages of the microRNA (miRNA) pathway for depletion of mRNA and suppression of protein translation. Primary and secondary structural characteristics that are shared between endogenous primary miRNA transcripts (pri-miRNAs) may contribute toward efficient biogenesis and potent silencing. This study investigates known miRNA transcripts for characteristics that are conserved between miRNAs and that distinguish them from rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 49 publications
3
34
0
1
Order By: Relevance
“…The flanking region, containing the mutation, may be important for proper tertiary structure of the stem-loop in the pre-mir. 35 This is consistent with the finding reported by others of decreased miR-16 in some patients with CLL. 33 One possible outcome of decreased miR-16 is a failure to properly reduce target gene expression.…”
Section: Linkage Analysis Of Murine Model Of Human B-cll 5083supporting
confidence: 93%
“…The flanking region, containing the mutation, may be important for proper tertiary structure of the stem-loop in the pre-mir. 35 This is consistent with the finding reported by others of decreased miR-16 in some patients with CLL. 33 One possible outcome of decreased miR-16 is a failure to properly reduce target gene expression.…”
Section: Linkage Analysis Of Murine Model Of Human B-cll 5083supporting
confidence: 93%
“…pri-miR-607. However, in the majority of the analyzed structures (62.6%) the SD junction was located 9-13 nt below the Drosha cleavage site which is in rough agreement with the consensus structure proposed by Han et al [9] and confirmed by Saetrom et al [28]. This region was shorter in 13% of the analyzed precursors and longer in 19.5% of the precursors ( Fig.…”
Section: Pri-mirna Structure and Droshasupporting
confidence: 89%
“…Most known animal miRNAs have a hairpin with a ϳ33 base pair stem flanked by a single-stranded region, and current models suggest that DGCR8 recognize this characteristic structure and guides Drosha to cleave the hairpin about 11 nts from the singlestranded region (33). Drosha or other unknown co-factors may, however, also recognize some of the miRNA hairpin's key features and thereby contribute to cleavage specificity (34,35). Second, the carrier protein Exportin-5 and Ran GTPase transport pre-miRNA from the nucleus to the cytoplasm (36 -38).…”
Section: Microrna Regulationmentioning
confidence: 99%